DEVELOPMENT OF A METHODOLOGY FOR STUDYING INDICATORS RELATED TO THE MEASUREMENT OF MAXILLARY SINUS THICKNESS, VOLUME USING LINEAR CALCULATIONS, AND DENSITY OF ITS COMPACT LAMINA BASED ON THE ANALYSIS OF A COMPUTED TOMOGRAPHY SCAN - Zaporozhchenko, V.M.; Tkachenko, I.M.; Dvornyk, A.V.; Gurzhiy, O.V.; Vodoriz, Y.Y. (World of Medicine and Biology, 2025)
Odontogenic maxillary sinusitis is a frequent complication of dental procedures, contributing to 25–40 % of chronic maxillary sinusitis cases and leading to a 10–20 % reduction in sinus volume. This necessitates precise morphometric evaluation. Using a NewTom GIANO HR scanner (voxel 0.1–0.2 mm), tomograms of 10 volunteers (aged 20–40) were analyzed. Linear measurements were taken with Ez3D tools; volume was calculated via ellipsoid and spherical models. The ellipsoid model proved more accurate (error 4–7 %) than the spherical one (8–12 %). The average sinus volume was 14.85 cm³. Cortical lamina density (HU) strongly correlated with its thickness (r > 0.9). The method is quick (≤5 min/patient), cost-effective, and suitable for routine clinical use. Correlation analysis supports its use in treatment planning, helping differentiate between surgical and conservative approaches. Further research should compare manual and automated CT analyses and assess mucosal thickness impact on sinus dynamics.